2018
DOI: 10.18535/jmscr/v6i4.53
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Practices Regarding Swine Flu among Individuals Attending Urban Health Centre in Medchal-Malkajgiri District, Telangana State

Abstract: Background: In April 2009, there were reports of sustained human-to-human infections with a new influenza A (H1N1) virus in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
1
5
0
Order By: Relevance
“…Also other studies like Bharadva et al in Bhuj, Shilpa et al 11,12 Singh et al, Anusha et al reported that more number of participants previously heard of swine flu 13,14. In this study, lower level of awareness among the rural people may be due to their illiteracy (53.9%).…”
supporting
confidence: 46%
See 2 more Smart Citations
“…Also other studies like Bharadva et al in Bhuj, Shilpa et al 11,12 Singh et al, Anusha et al reported that more number of participants previously heard of swine flu 13,14. In this study, lower level of awareness among the rural people may be due to their illiteracy (53.9%).…”
supporting
confidence: 46%
“…Dayanand et al found in their study, that 93% respondents were unaware about medicine to treat swine flu and 60.6% of them did not know about diagnostic test of swine flu. 15 10,11,14 In this study, preventive measures like covering the mouth and nose while coughing and sneezing, frequent hand washing with soap and water and to avoidance of crowded places and contact with sick people was known to 32 (54.23%) while 27 (45.8%) had no knowledge of preventive measures. Similarly In a study by Shilpa et al reported that use of mask/handkerchief as a preventive measure against swine flu was known to 81.5%, others said it could be prevented by maintaining personal hygiene 37.0%, avoiding crowded places 32.1% etc.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…[ 13 14 ] Mass media was the most common source of information about swine flu among study subjects quoted by Anusha et al . [ 15 ] and Naik et al . [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have recognized other symptoms that could be used as risk measurements of a COVID-19 infection such as sore throat, headache and myalgia (Ahmed and Ali, 2019; Anusha, 2018; Strunk et al , 2014). Aging and chronic diseases such as diabetes, organ and coagulation dysfunction, hypertension and neutrophilia were deemed as risk factors that exacerbate COVID-19 complications (Afzal et al , 2020; Ahmed and Ali, 2019; Deng and Peng, 2020; Sari et al , 2020).…”
Section: Introductionmentioning
confidence: 99%